PENGARUH KONSELING KELOMPOK TERHADAP PROKRASTINASI AKADEMIK SISWA - Nabila Azzahra; Ajeng Diah Rahmwati; Risma Anita Puriani (CV. ADIBA AISHA AMIRA, 2026)
Academic procrastination, or the habit of putting off assignments, is a common problem experienced by students and impacts academic achievement, motivation, and mental health. One approach used to address this problem is group counseling. Group counseling provides opportunities for students to discuss, share experiences, and support each other, thereby increasing motivation, self-management skills, and a sense of responsibility for academic tasks. This study used a journal review method, reviewing various previous studies that discussed the effectiveness of group counseling in reducing academic procrastination. The review results indicate that group counseling has been proven effective in reducing procrastination in both junior high and high school students. For junior high students, group counseling functions more as social support and external motivation, while for high school students, group counseling plays a more important role in strengthening self-efficacy and learning independence. Factors such as active member involvement, facilitator quality, and school support also influence the success of group counseling.